MANAJEMEN MODAL KERJA TINJAUAN EKONOMI ISLAM - Lestari, Linda; Ahmad, Luthfi Abdul Aziz; Aziz, Malik Abdul; Suryaman, A; Handayani, Susi (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
Every company activity will be tied to the problem of capital needs, so working capital management is an important part of efforts to optimize business operations. The study of this article covers elements of working capital, working capital management, and working capital management review of the Islamic economy. The writing method used is a qualitative approach to literature studies. Working capital management is an activity that includes the entire management role of current assets and current debt in an enterprise. The company's operational needs will be met with an adequate amount of working capital. The circulation period of working capital is from cash expenditures to short-term cash re-receipts. Working capital in the sharia sense is a valuable asset that is managed according to sharia rules with the aim of increasing productivity or business development on the basis of benefit. The concept of using working capital according to sharia that the assets used as capital must always rotate so as to create benefits for business actors. Meanwhile, the concept of sharia review working capital turnover is an effort to increase the amount of capital in accordance with sharia regulations through production or investment according to the expected objectives.